Improving Student Achievement in Qur’an Hadith Lessons Through Animated Videos - Martias Martias; Saleh bin Nur; Azamat Nazarov (Journal Emerging Technologies in Education, 2024)
Background. The development of Information and Communication Technology (ICT) in the world of education is increasing. Teachers are required to be more creative and innovative in choosing suitable media when delivering learning materials, one of which is animated videos. Animated videos are audiovisual media that can attract students’ attention and present objects in detail, making it easier for students to understand the learning material. Purpose. The purpose of this research is to improve student achievement in Qur’an Hadith lessons through animated videos. Another goal is to increase students’ motivation so that they do not feel bored or disinterested during the learning process. Method. The research method used is a quantitative approach with a survey model. Results. The research method used is a quantitative approach with a survey model. Conclusion. The limitation of this study is that the researcher only used animated videos for teaching Qur’an Hadith. The researcher hopes that future studies can conduct similar research with different subjects.